Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2737/pnw-gtr-694
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the challenge: invasive plants in Pacific Northwest ecosystems.

Abstract: PESTICIDE PRECAUTIONARY STATEMENTThis publication reports research involving pesticides. It does not contain recommendations for their use, nor does it imply that the uses discussed here have been registered. All uses of pesticides must be registered by appropriate state or federal agencies, or both, before they can be recommended.CAUTION: Pesticides can be injurious to humans, domestic and wild animals, and desirable plants if they are not handled or applied properly. Use all pesticides selectively and carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Throughout the Coast Range and Western Cascades, invasives dominate for the first 2-5 years following the disturbance but are then replaced by native species as succession progresses. This pattern was observed from 2001-2005 across the Forest Inventory and Analysis Program plots in Washington and Oregon mountain ranges (Harrington et al 2007). They found that the percentage of invasive species declined with increasing stand size class.…”
Section: Impactsmentioning
confidence: 79%
“…Throughout the Coast Range and Western Cascades, invasives dominate for the first 2-5 years following the disturbance but are then replaced by native species as succession progresses. This pattern was observed from 2001-2005 across the Forest Inventory and Analysis Program plots in Washington and Oregon mountain ranges (Harrington et al 2007). They found that the percentage of invasive species declined with increasing stand size class.…”
Section: Impactsmentioning
confidence: 79%
“…In a nonnative environment (i.e., California, USA), density of C. scoparius germinants declined exponentially during three growing seasons from about 770 to 32 seedlings m −2 , although the causes of mortality were not identified (Bossard and Rejmánek 1994). In harvested, thinned, and intact forests of coastal Douglas-fir in western Washington, USA, less than 2% of seeds produced seedlings of C. scoparius 2 yr after sowing (Harrington 2007). Paynter et al (1998) suggested that mortality of new seedlings under mature C. scoparius in France was attributable to a “rain” of invertebrate herbivores and pathogens; whereas in open areas, mortality was attributable to competition for light and soil water because new seedlings are relatively poor competitors.…”
Section: Resultsmentioning
confidence: 99%
“…Although typically found in open sites (Peterson and Prasad 1998), C. scoparius can establish and survive in conditions of low light availability (10% of full sun; Williams 1981), such as a forest understory (Harrington 2007). In its native range, C. scoparius requires disturbance of associated vegetation in order to regenerate successfully, because newly germinated seedlings are relatively poor competitors (Paynter et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Gray et al (2011) provide a field guide and prioritized list of nonnative plants along with range maps that cover the entire assessment area. More information on management of nonnative species is also available in Harrington and Reichard (2007).…”
Section: Biotic Disturbances-mentioning
confidence: 99%